Agilent Technologies, Inc: The Winning Strategies As A Technology Leader - Tan, Su In (2005)
This study aim to analyze Agilent's current business strategies against future position, to propose and recommend business strategies after benchmarking with other established company's business strategies in the same nature of business and literatures review. Ultimately, this study will evaluate if a generic business strategy across the organization should be introduced and developed to enable Agilent remains competitive as global technology leader.